Indentation Response of Calcium Aluminoborosilicate Glasses Subjected to Humid Aging and Hot Compression - Ren, Xiangting (Materials (Basel), 2021)
Aluminoborosilicate glasses find a wide range of applications, which require good mechanical reliability such as surface damage resistance. Calcium aluminoborosilicate (CABS) glasses have recently been found to exhibit so-called intermediate behavior in terms of their response to sharp contact loading. That is, these glasses deform with less shear than normal glass and less densification than anomalous glasses. This deformation mechanism is believed to give rise to high crack initiation resistance of certain CABS glasses. In order to further improve and understand the micromechanical properties of this glass family, we studied the indentation response of different CABS glasses subjected to two types of post-treatment, namely hot compression and humid aging. Upon hot compression, density, elastic moduli, and hardness increased. Specifically, elastic modulus increased by as much as 20% relative to the as-made sample, while the largest change in hardness was 1.8 GPa compared to the as-made sample after hot compression. The pressure-induced increase in these properties can be ascribed to the increase in network connectivity and bond density. On the other hand, the crack initiation resistance decreased, as the hot compression increased the residual stress driving the indentation cracking. Humid aging had only a minor impact on density, modulus, and hardness, but an observed decrease in crack initiation resistance. We discuss the correlations between hardness, density, crack resistance, and deformation mechanism and our study thus provides guidelines for tailoring the mechanical properties of oxide glasses.